Phytochemical profile, physicochemical, antioxidant and antimicrobial properties of Juniperus phoenicea and Tetraclinis articulate: in vitro and in silico approaches - Asbabou, Ayoub; Hanane, Touijer; Gourich, Aman Allah; Siddique, Farhan; Drioiche, Aziz; Remok, Firdaous; Saidi, Soukaina; Adadi, Imad; Khamar, Hamid; Almaary, Khalid S.; Mekonnen, Amare Bitew; Bourhia, Mohammed; et al. (Frontiers in Chemistry, 2024)
This research aims to explore the molecular composition, antioxidant capabilities, and antibacterial effects of the essential oils from Tetraclinis articulateata and Juniperus phoenicea. Essential oils were extracted using hydrodistillation. Gas chromatography combined with mass spectrometry was used to determine the chemical makeup of essential oils. The essential oil yields from Tetraclinis articulata and Juniperus phoenicea are 0.46 ± 0.02% and 0.83 ± 0.05%, respectively. According to CG/SM's chromatographic analyses, the predominant constituent in the essential oil of J. Phoenicea is α-pinène (59.51%), while the main constituents in the essential oil of T. Articulata are Bornyle acetate (18.91%) and camphor (28.48%). Two methods are used to assess the antioxidant activity of essential oils: the reduction of iron (ferric reducing antioxidant power or frap) and the trapping of the free radical 2,2-Diphenyl-1-Picrylhydrazyl (DPPH). The assessment of antioxidant activities reveals intriguing antioxidant qualities in the essential oils of the species under investigation.T. Articulata essential oils yield the greatest results in the DPPH and FRAP tests, with CI50 values of around 266.9 ± 5.4µg/ml and EC50 values of 433.16 ± 4.13µg/ml, respectively. The antimicrobial potential of essential oils was assessed using the diffusion method on a solidstate disk in comparison to nine bacterial and seven fungal souches. Except for Staphylococcus epidermidis, Staphylococcus aureus BLACT, and Pseudomonas aeroginosa, the two essential oils have demonstrated significant bactericidal activity against all bacterial and fungal souches (MIC < 2 mg/ml et MBC < 3,5 mg/ml). The inhibiting effect of these oils on bacterial and fungal development raises potential application areas in the food, cosmetic, and pharmaceutical industries. In addition, the current study investigated the potential antifungal, antibacterial, and antioxidant activities of the essential oils from Juniperus phoenicea and Tetraclinis articulate plants via the Glide molecular docking methodology, and most of these constituents were observed to be potent therapeutic agents.